Identidade cristã e pluralidade religiosa em Edward Schillebeeckx. - Santos, Faustino dos (2020)
This work addresses, from the reflection of the belgian dominican theologian Edward Schillebeeckx, two relevant and current themes in Christian theology: the question of Christian identity and the "problem" of religious plurality. It is proposed to show that the principle of openness to cultures and religions is constitutive of Christian identity, that is, it is based on faith and not in spite of it. Cultural and religious diversity must be recognized and respected from the Christian point of view. However, pluralism is not the fundamental reason for welcoming others. Rather, Jesus Christ himself welcomed all without distinction, without prejudice, for he did not live for himself but for the sake of the Reign of God, rooted in justice and care for the poor and marginalized. Moreover, if Jesus Christ himself as the full and definitive revelation of God is a decentralized reality, then Christianity, which wants to be constituted as his historical body, must take the same principle as a reference. In other words, Christianity must be decentralized from the alleged exclusivity and self-referentiality that accompanied it for many years in order to open itself to the practice of the Kingdom of God. This demands an attitude of welcome and openness. It must be borne in mind that the God of Jesus is a symbol of openness rather than closure. The historical contingency of Jesus of Nazareth as a limited manifestation of God's fullness does not exhaust his greatness but puts him in special relationship to the recognition and acceptance of divine values present in the world’s religions. Thus, pluralism is not an evil to be abolished; pluralism can offer a way for religion to serve as a tool to overcome petty strife and open conflicts that, all too often, are justified in terms of religious identity. It is a work, therefore, that gathers in Edward Schillebeeckx's thinking the reasons why Christianity can and should be optimistic with other religions without giving up its own identity and which, in the context of cultural and religious plurality, calls on Christianity to update your message in the world.